Reducing the impact of drought - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Living with drought. Drought mitigation for sustainable livelihoods. A von Kotze and A Holloway. David Philip Publishers-Intermediate Technology Publications copublication. 1999. 217 pp. + video. ISBN 0 86486 388 8/1 85339 470 X CTA number 923. 4